Analisis Gurindam Dua Belas Sebagai Salah Satu Peninggalan Sastra Islam Oleh Raja Ali Haji - Adinnda Intan Mulya Prayetno; Afdhal Kusumanegara; Diana Sapta; Nadia Shalsa Nabila; Renita Hastuti; Sella Marleoni (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Gurindam Dua Belas is a monumental work by Raja Ali Haji, one of the greatest writers in Riau. Even though Gurindam Dua Belas was written about two centuries ago, the depth of its meaning, the stunning beauty of its voice and content are still relevant and can be enjoyed. Gurindam 12 contains instructions for worship so that readers remain close to Allah SWT, the duties of kings, the nature of society, the duties of parents towards children and vice versa. Children's obligations to parents, and so on. This article describes human (moral) values ​​to preserve the character of a nation in the millennium era.